An Algorithm to reduce End to End Delay AND Enhance the Quality of Service in Mobile Adhoc Network - Ahirwal, Ramratan; Chaurasiya, Nitesh Kumar; Jain, Yogendra Kumar (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
A mobile adhoc network (MANET) is formed by a group of wireless mobile hosts or nodes without any fixed infrastructure. As there is no inner control in a MANET, a mobile node itself acts as a router. Undoubtedly, MANETs plays a critical job in situations where a wired infrastructure is neither available nor easy to install. Wireless mesh networks have large round trip time variations and these variations are dependent on the number of hops. The end-to-end throughput degrades rapidly with increase in number of hops. This is one of the biggest problems in MANET. In this paper we introduce an algorithm for avoiding congestion in MANETs. The algorithm demonstrates fast response and superior stability with the controlled packet dropping rate, and reduces end-to-end delay in MANETs, while still fully utilizing the network resources. Analysis and simulation show the strength and robustness of the algorithm. This method is simple and easy to use. We also illustrate the advantages of our proposed approach by comparing its results with standard AODV with recommended parameter settings.